PERSEPSI DAN SIKAP SISWA TENTANG KEGIATAN EKSTRAKURIKULER PRAMUKA - Pungki Randha Krisna; Mustiningsih Mustiningsih; Desi Eri Kusumaningrum (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2018)
ABSTRACT: The purpose of this study: (1) to describe the level of student perceptions about scout extracurricular activities; (2) to describe students' attitudes towards scout extracurricular activities; and (3) to examine the relationship between perceptions and attitudes of students regarding scout extracurricular activities. This research is included in the quantitative descriptive research with the Dwivariate Correlational research model. Data was collected using a questionnaire obtained from 4 state high schools located in the urban center of Bojonegoro district. The results of this research and development are: (1) Students' perceptions of the Scout extracurricular activities in State High Schools throughout the Bojonegoro District are in the Good category; (2) Students' attitudes about Scouting extracurricular activities in State High Schools throughout Bojonegoro District are in the Good category; and (3) The relationship between student perception variables and attitude variables related to the Scout extracurricular activities shows that a positive correlation in the State Senior High Schools in Bojonegoro Subdistrict.Key words: student perceptions, student attitudes, scout extracurricular activities ABSTRAK: Penelitian ini bertujuan, untuk: (1) mendeskripsikan tingkat persepsi siswa tentang kegiatan ekstrakurikuler pramuka; (2) mendeskripsikan sikap siswa terhadap kegiatan ekstrakurikuler pramuka; dan (3) menguji hubungan persepsi dan sikap siswa tentang kegiatan ekstrakurikuler pramuka. Penelitian ini termasuk dalam jenis penelitian Deskriptif Kuantitatif dengan model penelitian Korelasional Dwivariat. Data dikumpulkan dengan menggunakan angket yang diperoleh dari dari 4 SMA Negeri yang terletak di pusat perkotaan Kabupaten Bojonegoro. Hasil penelitian ini menunjukkan, bahwa: (1) Siswa SMAN di Kecamatan Bojonegoro memiliki tingkat persepsi baik tentang kegiatan ekstrakurikuler Pramuka; (2) Siswa SMAN di Kecamatan Bojonegoro memiliki sikap baik tentang kegiatan ekstrakurikuler Pramuka; dan (3) Ada hubungan positif antara persepsi dan sikap tentang kegiatan ekstrakurikuler Pramuka di SMA Negeri se-Kecamatan Bojonegoro.Kata Kunci: persepsi, sikap, kegiatan ekstrakurikuler pramuka